Soil Microbial Biomass Carbon under Rhizosphere and Non- Rhizosphere of Maize after a Long-Term Nitrogen Fertilization and Tillage Systems - Dermiyati, .; Firdaus, Eva; Utomo, Muhajir; Arif, Mas Achmad Syamsul; Nugroho, Sutopo Ghani (JOURNAL OF TROPICAL SOILS, 2011)
This research aimed to study the soil microbial biomass carbon (SMBC) under maize plant after a long-term application of nitrogen fertilizer and tillage systems (at the 37th growing season). The treatments were arranged in a factorial (3x3) in a randomized completely block design with 3 replications. The first factor was tillage systems, namely intensive tillage (IT) system, minimum tillage (MT) system, and no tillage (NT) system, and the second factor was the long-term application of nitrogen fertilizer, namely 0, 100, and 200 kg N ha-1. Data were analyzed using an orthogonal contrast test and a correlation test between SMBC and organic-C, total-N, and pH of the soil. The results showed that, in the rhizosphere and non-rhizosphere of maize plant, MT system increased the SMBC compared to NT and IT systems. However, application of long-term application of nitrogen fertilizer did not increase the SMBC. Nevertheless, fertilizer application of 100 kg N ha-1 increased the SMBC compare to 200 kg N ha-1.Furthermore, the combination of MT system and 100 kg N ha-1 could increase the SMBC compared to the other combined treatment between tillage systems and N fertilization doses. The SMBC was higher in the rhizosphere than in non-rhizosphere of maize plant.Keywords: Non-rhizosphere, rhizosphere, soil microbial biomass carbon, tillage systems